Identification of novel in vivo obligate GroEL/ES substrates based on data from a cell‐free proteomics approach. Issue 2 (5th January 2016) - Niwa, Tatsuya; Fujiwara, Kei; Taguchi, Hideki
Abstract : Chaperones are essential to maintain the proper folding of various proteins in vivo . The Escherichia coli chaperonin GroEL/GroES (GroE) is one of the best‐studied chaperones, and its in vivo substrates have been identified, mainly by mass spectrometry‐based proteomic studies. Here, we newly identified 20 in vivo obligate GroE substrates with the aid of data from an in vitro comprehensive analysis. The newly identified substrates have similar physicochemical properties to the known substrates, but their expression levels in vivo were significantly lower. Information from the in vitro comprehensive analysis has the potential to compensate for limitations of the MS‐based proteomic approaches. Abstract :